Effect of Temperature and Sisal Fiber Content on the Properties of Plaster of Paris - M. ALmusawi, Aqil; S. Hussein, Thulfiqar; A. Shallal, Muhaned (International Journal of Engineering and Technology, 2018)
Recent developments in the production of ecologically friendly building composites have led to a renewed interest in the use of vegetable fibers as a reinforcement element. Traditional pure Plaster of Paris (POP) can suffer from the development of micro-cracks due to thermal expansion. Therefore, sisal fiber was studied for its potential as an ecological element to restrict and delay the development of micro-cracks in POP. Different sisal proportions of 0, 2, 4, 6, 8 and 10 wt. % of POP were used to characterize the physical and mechanical properties of POP at the ambient temperature. Then, the effects of temperatures of 25, 100, 200, 300, 400 and 500 Â were investigated. Results proved that the composite of 10% sisal fiber had the best mechanical properties. Also, when the fiber content was increased, the compositeâ€™s performance was enhanced, becoming better able to resist elevated temperatures. However, raising the temperature to 300 or above had a negative effect on the mechanical properties, which were significantly decreased due to the degradation of the sisal fiber.Â